Inactivation of RPX1 in Arabidopsis confers resistance to Plutella xylostella through the accumulation of the homoterpene DMNT. (5th January 2023) - Chen, Hongyi; Chen, Chen; Huang, Shijie; Zhao, Mengjie; Wang, Tengyue; Jiang, Taoshan; Wang, Chuanhong; Tao, Zhen; Zhang, Yan; Wang, Yunhe; Wang, Wanyi; Tang, Qingfeng; et al.
Abstract: The lepidopteran crop pest Plutella xylostella causes severe constraints on Brassica cultivation. Here, we report a novel role for RPX1 (resistance to P. xylostella ) in resistance to this pest in Arabidopsis thaliana . The rpx1‐1 mutant repels P. xylostella larvae, and feeding on the rpx1‐1 mutant severely damages the peritrophic matrix structure in the midgut of the larvae, thereby negatively affecting larval growth and pupation. This resistance results from the accumulation of defence compounds, including the homoterpene (3 E )−4, 8‐dimethyl‐1, 3, 7‐nonatriene (DMNT), due to the upregulation of PENTACYCLIC TRITERPENE SYNTHASE 1 ( PEN1 ), which encodes a key DMNT biosynthetic enzyme. P. xylostella infestation and wounding induce RPX1 protein degradation, which may confer a rapid response to insect infestation. RPX1 inactivation and PEN1 overexpression are not associated with negative trade‐offs for plant growth but have much higher seed production than the wild‐type in the presence of P. xylostella infestation. This study offers a new strategy for plant molecular breeding against P. xylostella . Summary statement: Plutella xylostella pests show severely negative influence on plant growth and reproduction, and the identification of resistant genes is essential. This study reveals that inactivation of RPX1 confers significant resistance to the pest by enhancing PEN1 expression and accumulating the homoterpene DMNT in Arabidopsis thaliana .